Management of Guidance and Counseling Services: A Multi-Site in State Islamic Junior High Schools - Ifnaldi Ifnaldi; Amiruddin Siahaan; Abdurrahman Abdurrahman (JTP - Jurnal Teknologi Pendidikan, 2026)
This multi-site study aims to analyze the management of guidance and counseling (GC) at MTsN 1 and MTsN 3 Aceh Tengah, focusing on three management aspects: planning, implementation, and supervision. Using a qualitative approach, data were collected through observation, in-depth interviews, and documentation studies, and then analyzed continuously through data condensation, data presentation, and conclusion drawing to obtain a comprehensive understanding. The results indicate that the main difference lies in the methods of identifying needs, namely the Student Needs Questionnaire at MTsN 1 Aceh Tengah and the Problem Disclosure Instrument at MTsN 3 Aceh Tengah. However, the implementation mechanisms differ, in which MTsN 1 Aceh Tengah is more comprehensive by explicitly including the handling of high-achieving students in addition to students with problems, while MTsN 3 Aceh Tengah is more general. The implementation of core services (basic, responsive, specialization/career) also shows similarities. However, the focus of system support becomes a distinguishing factor. MTsN 1 Aceh Tengah prioritizes the implementation of assessment and follow-up, home visits, reporting, administration, and professional development of counselors. In contrast, MTsN 3 Aceh Tengah is oriented toward describing the dimensions of the Pancasila Student Profile, participation in the GC Subject Teacher Forum (MGMP BK), and self-development seminars. Finally, in supervision/evaluation, both madrasahs demonstrate the same commitment, namely focusing on the sustainable success of services.